MicroRNA-252 and FoxO repress inflammaging by a dual inhibitory mechanism on Dawdle-mediated TGF-β pathway in Drosophila. Issue 1 (21st December 2021) - Wu, Xiaofen; Niu, Kongyan; Wang, Xiaofan; Zhao, Jing; Wang, Han; Li, Dean; Wang, Hui; Miao, Ting; Yang, Yun; Ma, Huanhuan; Zhang, Yaoyang; Pan, Lei; et al.
Abstract: Inflammaging refers to low-grade, chronically activated innate immunity that has deleterious effects on healthy lifespan. However, little is known about the intrinsic signaling pathway that elicits innate immune genes during aging. Here, using Drosophila melanogaster, we profile the microRNA targetomes in young and aged animals, and reveal Dawdle, an activin-like ligand of the TGF-β pathway, as a physiological target of microRNA-252. We show that microRNA-252 cooperates with Forkhead box O, a conserved transcriptional factor implicated in aging, to repress Dawdle. Unopposed Dawdle triggers hyperactivation of innate immune genes coupled with a decline in organismal survival. Using adult muscle tissues, single-cell sequencing analysis describes that Dawdle and its downstream innate immune genes are expressed in distinct cell types, suggesting a cell nonautonomous mode of regulation. We further determine the genetic cascade by which Dawdle signaling leads to increased Kenny/IKKγ protein, which in turn activates Relish/NF-κB protein and consequentially innate immune genes. Finally, transgenic increase of microRNA-252 and Forkhead box O pathway factors in wild-type Drosophila extends lifespan and mitigates the induction of innate immune genes in aging. Together, we propose that microRNA-252 and Forkhead box O promote healthy longevity by cooperative inhibition on Dawdle-mediated inflammaging.